Revisiting firm flexibility and efficiency: evidence from the EU dairy processing industry. (11th March 2019) - Hirsch, Stefan; Mishra, Ashok; Möhring, Niklas; Finger, Robert
Abstract: We analyse the flexibility of EU dairy processors to adjust production to fluctuating economic conditions. For a set of 2, 186 firms, we derive production flexibility measures representing the effect of output variations on costs. The results reveal that flexibility is highest in Poland and Italy and lowest in Spain. Several firm-specific factors, such as size and age of the firm, are found to affect firm flexibility. Moreover, we detect a tradeoff between flexibility and technical efficiency for large firms indicating that a sole focus on firm efficiency can be insufficient. Finally, the results show that during economic crisis flexibility can help to sustain profitability.